ASSESSMENT OF THE QUALITY OF THE ACADEMIC STAFF OF KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN AND ITS SIGNIFICANCE: ASSESSMENT OF THE QUALITY OF THE ACADEMIC STAFF OF KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN AND ITS SIGNIFICANCE - Korneliya , Todorova (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The diagnostics analysis of the appraisal system of the academic staff of Shumen University is subject to formal and informal rules, requirements and procedures for the assessment of performance of faculty members as well as the conditions that are set up for this activity. The conducted empirical sociological study attempts to clarify the effectiveness of this system, considering the appraisal as a motivational factor for increasing productivity, improving quality of work and professional and qualification skills.